Particulate organic matter in the Lena River and its delta: from the permafrost catchment to the Arctic Ocean - O. Ogneva; O. Ogneva; O. Ogneva; G. Mollenhauer; G. Mollenhauer; B. Juhls; T. Sanders; J. Palmtag; J. Palmtag; M. Fuchs; H. Grotheer; P. J. Mann; et al. (Biogeosciences, 2023)
Rapid Arctic warming accelerates permafrost thaw, causing an additional release of terrestrial organic matter (OM) into rivers and, ultimately, after transport via deltas and estuaries, to the Arctic Ocean nearshore. The majority of our understanding of nearshore OM dynamics and fate has been developed from freshwater rivers despite the likely impact of highly dynamic estuarine and deltaic environments on the transformation, storage, and age of OM delivered to coastal waters. Here, we studied particulate organic carbon (POC) dynamics in the Lena River delta and compared them with POC dynamics in the Lena River main stem along a ∼ 1600 km long transect from Yakutsk, downstream to the delta. We measured POC, total suspended matter (TSM), and carbon isotopes (δ13C and Δ14C) in POC to compare riverine and deltaic OM composition and changes in OM source and fate during transport offshore. We found that TSM and POC concentrations decreased by 70 % during transit from the main stem to the delta and Arctic Ocean. We found deltaic POC to be strongly depleted in 13C relative to fluvial POC. Dual-carbon (Δ14C and δ13C) isotope mixing model analyses indicated a significant phytoplankton contribution to deltaic POC (∼ 68 ± 6 %) and suggested an additional input of permafrost-derived OM into deltaic waters (∼ 18 ± 4 % of deltaic POC originates from Pleistocene deposits vs. ∼ 5 ± 4 % in the river main stem). Despite the lower concentration of POC in the delta than in the main stem (0.41 ± 0.10 vs. 0.79 ± 0.30 mg L−1, respectively), the amount of POC derived from Yedoma deposits in deltaic waters was almost twice as large as the amount of POC of Yedoma origin in the main stem (0.07 ± 0.02 and 0.04 ± 0.02 mg L−1, respectively). We assert that estuarine and deltaic processes require consideration in order to correctly understand OM dynamics throughout Arctic nearshore coastal zones and how these processes may evolve under future climate-driven change.